Análisis socioeconómico del comercio informal por género y su impacto en la economía de las familias cantón El Empalme años 2008-2012 - Ruiz Aspiazu, Martha María (2015)
This research work was on analysing the informal trade by gender and its impact on the economy of the families, Canton el Empalme, year 2008 – 2012. Informal trade occurs due to lack of employment which leads to not have another exit to the work of informal activities, many people work from their own homes or small business or engage in domestic services. It is elementary to point out that the data was collected directly from informal traders Canton El Empalme through a questionnaire. For which were conducted several surveys to informal traders. Settled, once obtained the results, the factors that generate informal trade by gender in the Canton El Empalme little sources working with 35%, limited economic resources with a 33%, people without preparing some 32%. The main factors which affects the informal trade by genre is the scarcity of jobs, low incomes families and has no other way to solve their spending who opt for informal trade in order to satisfy your needs